Fetal Outcome in Primigravida Females Presenting with Breech Pregnancy at Term - Jamali, Kainat; Naz, Shabnam; Shaikh, Afsheen Shahid; Shaikh, Fozia; Paras; Jokhio, Shazmina (Indus Journal of Bioscience Research, 2025)
Introduction: Breech presentation, defined as the fetus being positioned with its buttocks or feet closest to the birth canal instead of the cephalic position, is a significant clinical concern, especially at term. Objective: The main objective of the study is to find the fetal outcome in primigravida females presenting with breech pregnancy at term. Methodology: This descriptive cross-sectional study was conducted in the Department of Obstetrics & Gynecology, Shaikh Zaid Women Hospital, Larkana, a tertiary care hospital from September, 2024 to May, 2025 providing comprehensive maternal and neonatal healthcare services. A detailed obstetric history and examination were performed, and findings were documented. The breech presentation was confirmed using ultrasonography. Results: The study included 100 primigravida females presenting with breech pregnancy at term. The mean age of the participants was 25.4 ± 3.2 years, with the majority (62%) aged between 20-30 years. The mean gestational age at delivery was 38.6 ± 1.1 weeks. Breech presentations were categorized as Frank Breech in 70% of cases and Complete Breech in 30%. Regarding delivery modes, 72% underwent cesarean sections, while 28% had vaginal breech deliveries. Poor Apgar scores (<7) at 1 minute were more common in vaginal breech deliveries (28.6%) compared to cesarean sections (13.9%), with a statistically significant p-value of 0.02. Conclusion: It is concluded that cesarean delivery is the safer option for primigravida females presenting with breech pregnancy at term, as it is associated with lower neonatal morbidity, reduced NICU admissions, and fewer birth injuries compared to vaginal breech delivery.